Community Empowerment of Parents Concerned about Adolescent Reproductive Health in Krucil District Probolinggo with CBR Approach (Community-Based Research) - Esti Novi Andyarini; Ika Mustika; Moch. Irfan Hadi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
Adolescence is a period of transition from childhood to adulthood. Teenager experience changes both physically and psychologically that are vulnerable to experiencing problems such as free sex, unwanted pregnancy, abortion, sexually transmitted diseases to early marriage. In Krucil District, Probolinggo, there are still many early marriages found. The marriage rate of less than 20 years in Krucil District is 61. Parents have an important role in determining child marriage. Formation The Community of Parents Caring for Adolescent Reproductive Health is expected to improve knowledge, attitudes and behavior of parents related to adolescent reproductive health so that they can prevent reproductive health problems. The method of community service that used is CBR (Community-Based Research). Devotion is done with empowering stakeholders in the community, namely health workers, educators and local community leaders. Establishment of a community of parents who care about reproductive health This is done by providing education and knowledge about reproductive health. After getting education, parents have good knowledge and there are changes attitudes and behavior of parents towards reproductive health. People are able to explain return the reproductive health materials that have been submitted. It is hoped that with this community, there is an increase in public knowledge about reproductive health and Changes in people's attitudes and behavior, especially in preventing health problems reproduction